Experimental Hybrid Ac/Dc-Microgrid Prototype for Laboratory Research - Espina-Gonzalez, E (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper describes a flexible testbed of a hybrid AC/DC microgrid developed for research purposes. The experimental setup is composed of 3 AC and 6 DC distributed generator units which are emulated by using three-legs inverters and settable output filters. The microgrid architecture allows to validate control schemes upstream of the modulation stage of each inverter, by using real-time targets and Mat-lab/Simulink interface. Two independent real-time communication networks can be used. The first one is based on optical fibre technology, whereas the second one is an Ethercat communication network. Both of them are used for instrumentation purposes and to implement the primary control level of the microgrid. To implement secondary control schemes into the microgrid (or higher control levels), an additional optical fibre-based network is used, allowing to emulate scenarios with or without communication issues such as latency, data-losses and topology changes. The built microgrid can be splitted into AC-side (3 and/or 4 wires), DC-side and interlinking-side, where both the AC and the DC side can be operated independently, according to the required electrical topology. In this testbed, several control schemes, such as proportional-integral, proportional-resonant or predictive controllers, have been investigated. Realised experimental tests include load changes, plug-and-play and communication issues scenarios. © 2020 EPE Association.
Keywords: AC/DC microgrid; Experimental prototype; Hybrid microgrid; Laboratory research; Testbed microgrid